2008
DOI: 10.1128/mcb.00323-08
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Complex 2 Is Required for E-cadherin Repression by the Snail1 Transcription Factor

Abstract: The transcriptional factor Snail1 is a repressor of E-cadherin (CDH1) gene expression essential for triggering epithelial-mesenchymal transition. Snail1 represses CDH1, directly binding its promoter and inducing the synthesis of the Zeb1 repressor. In this article, we show that repression of CDH1 by Snail1, but not by Zeb1, is dependent on the activity of Polycomb repressive complex 2 (PRC2). Embryonic stem (ES) cells null for Suz12, one of the components of PRC2, show higher levels of Cdh1 mRNA than control E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
324
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 397 publications
(340 citation statements)
references
References 42 publications
11
324
5
Order By: Relevance
“…Therefore, it is not difficult to understand why siSnail, but not siYY1 dissociated EZH2 and HDAC1/2 from the YY1 region of Ecadherin promoter. As a result of our collective present data, together with other group's findings (van der Vlag and Otte, 1999;Peinado et al, 2004;Herranz et al, 2008;von Burstin et al, 2009), herein we propose a main co-repressor complex, that is, EZH2/HDAC1/2/Snail, in the regulation of E-cadherin in NPC cells, and probably in a number of other types of human cancers. A schematic representation of the major molecular mechanisms of this complex, in NPC cells, is suggested and provided in Figure 5d.…”
Section: Ezh2 Promotes Npc Cell Aggressiveness Z-t Tong Et Alsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, it is not difficult to understand why siSnail, but not siYY1 dissociated EZH2 and HDAC1/2 from the YY1 region of Ecadherin promoter. As a result of our collective present data, together with other group's findings (van der Vlag and Otte, 1999;Peinado et al, 2004;Herranz et al, 2008;von Burstin et al, 2009), herein we propose a main co-repressor complex, that is, EZH2/HDAC1/2/Snail, in the regulation of E-cadherin in NPC cells, and probably in a number of other types of human cancers. A schematic representation of the major molecular mechanisms of this complex, in NPC cells, is suggested and provided in Figure 5d.…”
Section: Ezh2 Promotes Npc Cell Aggressiveness Z-t Tong Et Alsupporting
confidence: 84%
“…Recently, Herranz et al (2008) found that zinc-finger factor Snail could recruit PRC2 complex to the E-cadherin promoter (Herranz et al, 2008). In this study, we found that the repressive activity of EZH2 in E-cadherin expression was virtually completely prevented, when Snail was knocked down in NPC cells.…”
Section: Ezh2 Promotes Npc Cell Aggressiveness Z-t Tong Et Almentioning
confidence: 54%
See 1 more Smart Citation
“…Accumulating evidences suggest that some regulatory elements, such as transcription factors and non-coding RNAs, may recruit certain enzymes to specific DNA regions (34). For example, the transcription factor SNAIL1 recruits to the Ecadherin promoter region histone demethylase LSD1 that removes H3K4me2 (35), histone deacetylase 1 (HDAC1) and HDAC2 (36), and PRC2, an H3K27me3 methyltransferase (37). In addition, some enzymes, e.g.…”
Section: Insert Figurementioning
confidence: 99%
“…Repression of E-cadherin is a molecular marker of EMT. Studies have demonstrated that EZH2 and Suz12 mediate transcriptional silencing of the tumor suppressor gene E-cadherin by trimethylation of histone H3 lysine 27 [14,15], which promotes the metastasis of cancer. These observations provide a functional link between the dysregulation of PRC2 and the repression of E-cadherin during cancer progression.…”
Section: Epithelial Mesenchymal Transitionmentioning
confidence: 99%